Agama dan Alam dari Perspektif Arne Naess - Barnabas Ohoiwutun (Sekolah Tinggi Filsafat Seminari Pineleng, 2022)
This article aims to explain on Arne Naess’ notion of relation between religion and nature. For Naess, relation between religion and nature has double face. On the one hand, religion is a good source for human being in understanding nature and himself. Religion teaches man how to creates a mutual relation with nature. On the other hand, religion is also the source of ecological crisis since through biblical interpretation which is anthropological oriented gives man knowledge and power to control even exploits nature wantonly. Therefore, to stop ecological crisis we need to shift our anthropological interpretation to an ecological interpretation. Using descriptive and analysis method, this study hopes to contribute on understanding of Naess’ concept on relation between religion and nature.